Simulation Analysis of Meshing Characteristic for Cycloid Meshing Drive of RV Reducer - Han Ju; Wang Xiaohu; Liang Liming (Jixie chuandong)
The cycloid pin wheel drive is essential to RV reducer. It is the basic point to determine the contact stiffness of cycloid and pin wheel. The equivalent contact stiffness is calculated based on Hertz contact theory. The parameters to solve the contact stiffness is checked and the stiffness model with teeth number in meshing simultaneously as a parameter is established. The dynamics simulation of RV reducer is processed based ADAMS to determine the pin numbers in meshing in consideration of modification of cycloid and dimension error of pin-wheel circle diameter,furthermore,the model of cycloid is treated as flexible body. It can be intuitive to observe the relations between load and number of pins in meshing or pin force.